Antiphospholipid scoring: significance in diagnosis and prognosis. (October 2014) - Oku, K; Amengual, O; Atsumi, T
Recently our group introduced the "antiphospholipid score" (aPL-S), a quantitative marker that represents aPL profile. We have validated its efficacy for the diagnosis of antiphospholipid syndrome (APS) and predictive value for thrombosis. The study comprised two independent sets of patients with autoimmune diseases. In the first set of patients ( n = 233), the aPL-S was established by analyzing aPL profiles. In the second set of patients ( n = 411), the predictive value of the aPL-S for thrombosis was evaluated. To define aPL-S, we calculated the relative risks (approximated by odds ratios (ORs)) of having APS manifestations (thrombosis and/or pregnancy morbidity) for each of the aPL tests and devised an original formula in which aPL-S was determined by OR: aPL-S = 5 × exp ([OR] −5)/4. The receiver operating characteristic (ROC) curve showed a hyperbolic pattern and the area under the ROC curve value was 0.752 (0.686 for revised Sapporo criteria), implying that aPL-S is a potential quantitative marker for APS diagnosis. The OR for thrombosis in patients with a high aPL-S (≥30) was 5.27 (95% confidence interval (95% CI) 2.32–11.95, p < 0.0001). By multivariate analysis, an aPL-S of ≥30 appeared to be an independent risk factor for thrombosis (hazard ratio 3.144 (95% CI 1.383–7.150), p = 0.006). The aPL-S is a useful quantitative index for diagnosing APS and may be a predictive marker for thrombosis in autoimmune diseases.